Digitalisasi Materi Ajar PAI Berbasis Multimedia Interaktif untuk Meningkatkan Minat Belajar Siswa - Fajtriansyah, Apriani; Merlianda, Dika; Neni (Sekolah Tinggi Agama Islam (STAI) AL-IKHLAS DAIRI SIDIKALANG, 2025)
This study aims to analyze how the digitization of interactive multimedia-based Islamic Education (PAI) teaching materials can increase student interest in learning and strengthen Islamic values in the digital age. Using a descriptive-qualitative library research approach, this study collects and reviews various literature in the form of books, journals, and research results on digital learning, multimedia theory, and modern PAI learning. Data analysis is carried out using content analysis techniques by examining the concepts of digitization, interactive multimedia, and their implications for the learning process and internalization of Islamic values. The results show that the digitization of PAI teaching materials can improve the accessibility, interactivity, and relevance of learning for Generations Z and Alpha. Interactive multimedia has been proven to strengthen students' understanding through a combination of text, visuals, audio, and simulations, in line with Mayer's Multimedia Learning Theory. In addition, digitization is also able to instill Islamic values such as trustworthiness, honesty, discipline, and religious moderation through contextual and engaging digital media. However, various challenges such as low digital literacy among teachers, infrastructure limitations, and potential cognitive load need to be overcome through appropriate training and pedagogical design. Overall, the digitization of interactive multimedia-based PAI teaching materials is an effective strategy for improving the quality of learning while strengthening the character and spirituality of students in the technological era.